Semiotic of Public Service Advertisement - Sumbo Tinarbuko (The Indonesian Journal of Communication Studies, 2008)
The public service advertising works have a sign that are verbal (language) and visual forms. Its also refer that the public service advertising text and its visual offering contents of an icon that has function, mainly in a system of non-language to support the massage of language, so the semiotics approach as a standard analytic method for analyzing the public service advertising works appropriates to be used and responded proactively as same